(untitled) (International Journal of Medical and Surgical Sciences, 2020)
Primary splenic lymphomas involve the spleen and/or its lymph nodes. They represent <1% of lymphomas and they imply a diagnostic challenge due to its poor symptomatology and low prevalence. There for, the objects this work describe the management and evolution of a patient with HIVAIDS and presentation of a primary lymphoma of the spleen. In this report we present the case of a 52-year-old male patient with HIV infection without treatment presented with abdominal pain, fever and a 2-month weight loss. The pre-operative computed tomography showed splenomegaly and hypodense lesions suspected to be tumoral. He was operated on, performing an exploratory laparotomy, performing an splenectomy. The histopathological study reported a non-Hodgkin lymphoma. Primary splenic lymphoma is a non frequent entity. It is necessary to be acquainted with it in order to suspect it.